Effect of Piper Nigrum fruit and Syzygium aromaticum roses extract on the some of Bacterial and fungal isolate growth - Mohammed Jafeer, Khulood Abed-Majeed; Kheirallah, Enass Abbass (Al-Qadisiyah Journal of Pure Science, 2017)
This research was conducted to evaluate the efficiency of hot water extracts of the fruits Piper nigrum and Syzygiumaromaticum in the inhibition of fungi and pathogenic bacteria. Where Results showed that hot water extract of Piper nigrumcaused 100% inhibition of fungi Aspergillusterrus, Candida albicans, Pencilliumspp.While it did not show any effect on other fungi under studied, results showed hot water extract of Syzygiumaromaticumcauses high percentage of inhibition of the direction of all fungi studiedat all concentrations except yeast Rhototorullaspp was attributed 50% inhibition concentration 50 mg / ml. The resist of bacteria tendency of some antibiotics and aqueous extract each of the plant Syzygium aromaticumand Piper nigrum has demonstrated a difference between the types of bacteria where damped antibiotic Alarthuromaysan bacteria Salmonella, Staphylococcus rate of diameter inhibition of 1 cm, either to extract hot water for the cloves where not recorded bacteria Proteus any effect in concentrations of 100 and 75 mg / ml. Compared bacterium Streptococcus pneumonia, where the rate recorded diameter inhibition 3,3.5, 4.5 in three concentrations, while Piper nigrum extract was given to the bacterium Staphylococcus aureusdiameter inhibition rate of 2.5 in the third focus either in the concentration of 100 and 75 mg / ml did not record any effect .